REDESIGN LIVING PHARMACY PARK, KALI ANYAR VILLAGE, TAMBORA SUBDISTRICT, WEST JAKARTA - Retna Ayu Puspatarini; Nabilah Nabilah; Sri Handjajanti (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2021)
Living pharmacy park in Sub village (SV) 007, Sub-sub village (SSV) 04, Kali Anyar Village, Tambora District located in West Jakarta is the location of Community Service activities. This activity was carried out gradually starting from before the Indonesian government issued a new order rule (New Normal) until the government issued new normal rules due to the Covid-19 pandemic. With the New Normal rules provide changes to the design of a living pharmacy park that has been designed before. This article aims to express the changes that occurred in the design of the living pharmacy park. The methods carried out are participatory methods and qualitative methods that are described descriptively. This article discusses the changing design sections that are adapted to the distance keeping rules. Redesign living pharmacy park is a work that combines design with the rules of New Normal covid 19.